Implementasi Digital Marketing pada UMKM Ucu Ema di Bengkalis - Hanim Inayati; Muhammad Arif; Nofiar.Am, Andri (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2025)
The purpose of this community service project is to implement a digital marketing strategy for Ucu Ema MSMEs in Bengkalis by applying the STP approach (segmenting, targeting, and positioning) and conducting a SWOT analysis (strengths, weaknesses, opportunities, threats). This activity also aims to identify challenges faced in digital marketing and provide appropriate solutions to improve business competitiveness. The method used consists of three main stages: preparation, implementation, and reporting of the community service activities. The results show a significant improvement in digital marketing performance through various social media platforms such as WhatsApp, Instagram (@umkm_ucuemaa), Facebook (Umkm Ucu Ema), and the Shopee marketplace (umkm_ucu_ema). This improvement has positively impacted sales and customer reach. The main challenge encountered was understanding the type of content preferred by the audience. The implemented solution involved adjusting content strategies according to user trends and preferences, making promotions more engaging and effective, and ultimately increasing consumer interest in Ucu Ema MSMEs products.